2014
DOI: 10.1007/s11663-014-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behaviors of CaO-SiO2-Al2O3-Na2O-CaF2-(Li2O-B2O3) Mold Fluxes

Abstract: Both the Matusita equation and the modified Matusita equation for estimating the activation energy associated with non-isothermal crystallization were critically evaluated. The derivation for melts crystallization on cooling indicates that, unlike for the crystallization that occurs on heating, the term 1 À exp (ÀDG/RT) in the basic rate equation of crystal growth and the term R T s 0 exp ÀE=RT ð Þ dT depending on the initial temperature of the cooling process cannot be neglected. It is demonstrated that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 44 publications
(52 reference statements)
6
44
1
4
Order By: Relevance
“…This result is also in accordance with the findings that the crystallization temperatures of CaO-SiO 2 -CaF 2 -based mold fluxes decrease with the decrease in the mold flux basicity (mass pct CaO/mass pct SiO 2 ). [9,21,22] It is clear from Figure 5(b) that the crystallization temperature of the second crystalline phase CaF 2 in the SiO 2 -free slag is much higher than those in the SiO 2 -containing slags. For CaF 2 -CaOAl 2 O 3 -SiO 2 slags, it appears that increasing SiO 2 addition from 2.8 to 6.8 mass pct has no noticeable effect on the crystallization temperature of the second crystalline phase formed in these slags, as shown in Figure 5(b).…”
Section: B Crystallization Temperatures and Crystallization Ability mentioning
confidence: 97%
See 1 more Smart Citation
“…This result is also in accordance with the findings that the crystallization temperatures of CaO-SiO 2 -CaF 2 -based mold fluxes decrease with the decrease in the mold flux basicity (mass pct CaO/mass pct SiO 2 ). [9,21,22] It is clear from Figure 5(b) that the crystallization temperature of the second crystalline phase CaF 2 in the SiO 2 -free slag is much higher than those in the SiO 2 -containing slags. For CaF 2 -CaOAl 2 O 3 -SiO 2 slags, it appears that increasing SiO 2 addition from 2.8 to 6.8 mass pct has no noticeable effect on the crystallization temperature of the second crystalline phase formed in these slags, as shown in Figure 5(b).…”
Section: B Crystallization Temperatures and Crystallization Ability mentioning
confidence: 97%
“…The results obtained here are consistent with the findings for mold fluxes reported by the present authors. [19,21] Figure 5 shows the CCT diagrams of the first and second crystalline phases precipitated from the slags containing different amounts of SiO 2 , respectively. The crystallization temperatures of the first crystalline phases 11CaOAE7Al 2 O 3 AECaF 2 are observed to decrease with increasing SiO 2 contents in the slag, as shown in Figure 5(a).…”
Section: B Crystallization Temperatures and Crystallization Ability mentioning
confidence: 99%
“…[13,14] Figure 4 shows the morphology of cuspidine crystal after iso-thermal DSC measurement at different crystallization temperatures for Slag B and D, and Table IV lists their supercooling, Jackson a factor, and corresponding crystal morphology. It should be pointed out that only cuspidine is present at the iso-thermal experimental temperatures since the second phase, i.e., wollastonite, precipitates at very low temperature for slag B according to the XRD identified results as shown in Table II Table IV that cuspidine of melt crystallization in slag B and D have a very similar Jackson a factor, but the undercooling for crystallization of slag B is much greater than that of slag D. Therefore, it can be concluded that the crystal morphology difference between Slag B and Slag D is mainly due to the supercooling difference rather than Jackson a factor.…”
Section: Cuspidine Morphology In Lime-silica-based Mold Fluxesmentioning
confidence: 99%
“…But their experimental results also demonstrated that lubrication and flux consumption of lime-alumina-based mold fluxes should be further improved for industrial applicability. In order to understand the causes of lubrication differences between lime-alumina-based mold fluxes and lime-silica-based mold flux further, more careful researches concerning on the crystallization behaviors had been carried out by the present authors, [13][14][15][16] which demonstrated huge differences in crystal morphology between the foregoing two kinds of mold fluxes, as shown in Figure 1. For the CaO-SiO 2 -based mold fluxes, the primary crystalline cuspidine (Ca 4 Si 2 F 2 O 7 ) was typically faceted with moderate size in morphology generally, as shown in Figure 1(a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation